Development of an Active Follow-up Process in a Stand-alone Medication Therapy Management (MTM) Clinic - Keri D. Hager (University of Minnesota Libraries Publishing, 2013)
Without following-up with patients, one cannot determine the outcomes of interventions made with patients. To ensure follow-up was occurring in a stand-alone MTM clinic, a process for active follow-up and an easy-to-use way to trigger and document follow-up was developed.   Type: Clinical Experience